Penyelesaian Sengketa Tanah Melalui Mediasi di Kantor Pertanahan Kabupaten Indragiri Hilir - M Rizqi (Jurnal Hukum Lex Generalis, 2025)
Land disputes in Indonesia reached 12,000 cases in 2024, promoting mediation as alternative resolution. This research analyzes implementation of ATR/BPN Minister Regulation No. 21/2020 in Indragiri Hilir Regency using empirical juridical method. Causal factors include administrative data inaccuracy, technical errors, low public legal awareness, and land economic value changes. Mediation process conducted through five systematic stages with Land Office as neutral facilitator. Main obstacles are parties' bad faith and institutional limitations, addressed through mediator capacity building and socialization programs. Mediation success rate reached 67% from 9 cases during 2021-2023 period.